Haematological Pattern of Children with Malaria Attending Paediatric OPD at Tertiary Care Hospital - Abdul RehmanSiyal , Fouzia Sheikh , MunwarAbbasi , Sumair Memon , Abdul RehmanSiyal , Fouzia Sheikh , MunwarAbbasi , Sumair Memon (Journal of Rawalpindi Medical College, 2019)
Objective: To determine the haematological pattern among children attending Paediatric OPD with diagnosis of malaria at tertiary care Hospital Methods: In this observational study children with diagnosis of malaria, age of <12 years and either of gender were enrolled. Each patient underwent clinical examination and medical history regarding duration of fever including sign/symptoms and previous antimalarial treatment history. Three ml blood was collected from all the patients for the complete blood count (CBC) The haematological abnormalities were recorded. Entire data was gathered and filled in the profrorma and its analysis was done by SPSS version 16.0. Results: Total 106 children were selected .Mean age was 5.31+2.47 years. Malarial infection was higher among male children 67(63.20%). Vivax parasite was most common among (53.80%),falciparum in 45.30%, while both parasites were found only in one case. Mean platelet count was 96.35+74.34 in children infected by falciparum malaria and 89.05+70.0 in vivax infected children (p-value=0.815). Mean haemoglobin level was 9.43+0.91 in falciparum malaria and 9.38+0.90 in vivax infection(p-value= 0.477). Mean WBC level was 5.81+1.35 in falciparum infected children and 6.06+1.41 in vivax infected children( p-value=0.614). There was no significant difference in haemoglobin and WBC according to parasites p-values were insignificant. Conclusion: Plasmodium vivax was the commonest parasite; male children remained on high risk of malarial transmission. Haematological changes markedly appeared but statistically insignificant according to falciparum and vivax.